A fully-packaged and robust hybridized generator for harvesting vertical rotation energy in broad frequency band and building up self-powered wireless systems. (March 2017) - Chen, Jie; Guo, Hengyu; Liu, Guanlin; Wang, Xue; Xi, Yi; Javed, Muhammad Sufyan; Hu, Chenguo
Abstract: Harvesting energies from surroundings to build up self-powered sensing systems is very useful in our daily life. In this work, we design a cylinder-like fully-packaged hybrid nanogenerator for harvesting vertical rotation energy in broad frequency band by utilizing a magnet rod as the trigger to drive contact-separation mode triboelectric nanogenerator (TENG), and by coupling magnet rod with copper coils to operate electromagnetic generator (EMG). The stator-free structure makes the device more facile to be installed on the rotation objects. The output performances of TENG and EMG under various rotation speeds are systematically studied and clearly demonstrated by installing the device on a balance car, which proves that TENG can be more effective for low-frequency (<2 Hz) energy scavenging and indicates the durability of the device can be largely enhanced with this structure design. In addition, the hybridized device is applied for harvesting wheel rotation energy from a car to drive wireless sensors for monitoring temperature, humidity, speed or even tire pressure simultaneously. This work presents a new platform of hybrid generators for harvesting rotation energy in broad frequency band and building up self-powered wireless sensing systems. Graphical abstracts: We reported a cylinder-like fully-packaged hybrid nanogenerator for harvesting vertical rotation energy in broad frequency band and building up self-powered wireless systems. Utilizing a magnet rod as the trigger to drive CS-TENG can largely enhance the durability of the device and the stator free structure makes the device more facile to be installed on the rotation objects. Highlights: The stator-free structure makes the device more facile to be installed on the rotation objects. Combing TENG and EMG, the hybridized device can effectively harvest broad frequency band rotation energy. TENG part would be stopped working when rotation speed rising to ~380 rpm due to the centrifugal force, which can largely improve the durability of the device. Fully-enclosed structure makes the device capable of operating in harsh environment. Demonstrated applications in wireless speedometer and thermo-hygrometer self-powered systems.